CONJUNCTIVITIS INFECTION: A BRIEF REVIEW ON ITS CLASSIFICATION, ETIOLOGY AND THERAPEUTIC INTERVENTIONS - ZULFIQAR , M; RAFIQUE , S; HABIB , A; QADER , A; ASGHAR, A; RIAZ, R (Biological and Clinical Sciences Research Journal, 2024)
Conjunctivitis is a common inflammatory disease in humans, and it has different types of categories, such as acute, chronic, infectious, and noninfectious. Conjunctivitis may break as an epidemic in different areas of the world. It causes discomfort in the eyes. Some signs and symptoms like redness of the eye, eye discharge, grittiness of the eyes, and lashes sticking together may appear. Based on etiologic agents, conjunctivitis is classified as viral conjunctivitis, bacterial conjunctivitis, allergic conjunctivitis, follicular conjunctivitis, and neonatal conjunctivitis. It may be due to contact with people having eye infections. Many strains of bacteria, viruses, and allergens cause different types of conjunctivitis. Many treatment strategies are applied to treat various kinds of conjunctivitis worldwide. Usually, antibiotics are used for the treatment of conjunctivitis, such as ophthalmic ointments erythromycin, chloramphenicol, and fusidic acid treatment. As a home remedy, many people wash their eyes with normal saline and water to reduce the duration of eye diseases.